СУРХОН ВОҲАСИДА ТУРИЗМ СОҲАСИНИ РИВОЖЛАНТИРИШ ИСТИҚБОЛЛАРИ (Journal of Universal Science Research, 2023)
The article outlines a number of proposals for the development of tourism in the Surkhandarya region, as well as the existing problems, the service delivery system, and human resource issues. Proposal for the visit to the region and the development of medical tourism, as well as proposals for the creation of the "Old Village" tourism as a new direction.